The Noteworthiness of Constructive Feedback and Student-Reflection to Approach Competence-Based Curriculum: An Explanatory Study of Medical Schools in Indonesia - Salamy, Achmad Yarziq Mubarak Salis; Claramita, Mora; Suhoyo, Yoyo (Universitas Gadjah Mada, 2024)
Background: Competence-based medical curriculum requires the acquisition of complex abilities that should be assessed longitudinally. The programmatic assessment model can facilitate a complete picture of students' competencies. The five components of learning, assessment, supporting activities; and intermediate to final evaluation provide holistic learning experiences for students and mentors to participate in the learning strategies. We aim to assess the application of longitudinal components of the programmatic assessment model to the current assessment system based on student perceptions.Methods: This study used a cross-sectional mixed-method sequential explanatory design at six medical schools in Surabaya, East Java of Indonesia. The instrument was 43 items of validated questionnaire based on the five components and the focus group discussions. Results: This study obtained 442 respondents. The results reflected high reliability with a Cronbach alpha value of 0.969, and the validity test showed R arithmetic > R table (R table 0.128 for n 442). The current assessment system was perceived as ‘good’, with 3.9 on 5 points Likert scale; but the ‘supporting activities’ where reflection and feedback lied; was at the lowest score although insignificant. Students underlined the lack of formative aspects (reflection, feedback, mentorship, and middle evaluation).Conclusion: The overall assessment system is well-perceived by the students; however, the 'supportive activities' component has been minimally applied. So the 'assessment of previous learning' is still prominent in the current assessment system.